Pelvic Organ Prolapse in Ehlers-Danlos Syndrome. (23rd February 2023) - Nazemi, Azadeh; Shapiro, Katherine; Nagpal, Shavy; Rosenblum, Nirit; Brucker, Benjamin M.
Abstract : Ehlers-Danlos syndrome (EDS) is a hereditary tissue and collagen synthesis disorder that can predispose patients to gynecologic and obstetric complications. Female patients often suffer from bothersome pelvic floor disorders, but due to the medical complexity of EDS, special considerations are needed for the treatment of pelvic organ prolapse and associated incontinence. In this paper, we present three unique cases of pelvic organ prolapse (POP) in EDS patients and delve deeper into the multidisciplinary approach involving urogynecology, rheumatology, physiatry, gastroenterology, and anesthesiology required to appropriately manage this condition.